791 A phase II study of the anti-programmed cell death-1 (PD-1) antibody penpulimab in patients with relapsed or refractory classic hodgkin lymphoma (cHL). (9th November 2020) - Song, Yuqin; Zhou, Keshu; Jin, Chuan; Qian, Zhengzi; Hou, Ming; Fan, Lei; Li, Fei; Ding, Kaiyang; Zhou, Hui; Li, Xiaoling; Chen, Bing; Sun, Xiuhua; et al.
Abstract : Background: Penpulimab is a humanized IgG1 mAb that blocks PD-1 binding to PD-L1. Penpulimab was engineered to eliminate Fc?R binding and ADCC/ADCP completely, as compared to majority of marketed IgG4 PD-1 antibodies with ADCC/ADCP activity. ADCC/ADCP effects can induce T-cell apoptosis and clearance and then compromise anti-tumor activity. The removal of Fc?R binding eliminates Fc receptor mediated immune-cell recruitment and activation and could potentially reduce immune-related adverse reactions. Penpulimab demonstrated a slower PD-1 antigen binding off-rate than marketed PD-1 antibodies, which result in better cellular activity and higher receptor occupancy. Penpulimab also showed numerous contacts with N58 glycosylation on the BC loop of PD-1 which could be an advantage to facilitate interaction of PD-1 antibody and may contribute to slower binding off-rate. These structural differentiations offer more robust biological effect and enhance anti-tumor activity of penpulimab. Methods: AK105-201 (NCT03722147 ) is a multicenter, single-arm, open-label study of penpulimab in R/R cHL. All pts received penpulimab 200 mg q2w until progression or unacceptable toxicity. Eligible pts had R/R cHL after ASCT, or at least 2 lines of prior chemotherapy. The primary endpoint was ORR based on the Lugano 2014 criteria as assessed by an independent review committee (IRC). Key secondary endpoints included CR rate, DCR, PFS, duration of response (DoR), safety, and tolerability. Results: As of 10 January, 2020, the median follow-up was 6.3 months (range, 3.5 to 17.0). The anti-tumor activity of penpulimab in the 73 pts evaluable for efficacy (defined as pts who had an opportunity to be followed for at least 16 weeks) is shown in the table 1. At data cutoff, 91.8% of responders remained ongoing and still on treatment. Treatment-related adverse events (TRAEs) occurred in 93.6% of pts (G3 in 13.8% [13/94], no G4 or G5, treatment discontinuation in 2.1% [2/94]). Treatment-related SAEs occurred in 3.2%. Most frequent TRAEs (≥15%) were fever (24.5%), hypothyroidism (21.3%), upper respiratory tract infection (18.1%), and ALT elevations (17.0%). Grade ≥3 TRAEs reported in ≥2 pts were platelet count decreased (2.1%). Immune-related AEs were reported in 42.6% of pts (G3 in 2.1%: psoriasis [n=1], IgA nephropathy [n=1]). Conclusions: Penpulimab was shown to be highly active resulting in a high CR rate in pts with R/R cHL. With longer follow-up, CR rate for penpulimab in R/R cHL could be further increased. Penpulimab demonstrated notably lower rates of SAE, TRAE leading to discontinuation, and Grade Grade ≥3 immune-related AEs in pts with R/R cHL. Trial Registration: NCT03722147